2012
DOI: 10.1097/bpo.0b013e318269c898
|View full text |Cite
|
Sign up to set email alerts
|

Hand and Upper Limb Anomalies in Poland Syndrome

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…Our findings that over 53 % of the patients were “normal presentation” patients concurs with previously published reports that a majority of elective referrals to paediatric orthopaedic specialists are for variants of normal development [ 33 ], and most are discharged after initial consultation [ 1 , 2 , 6 – 9 , 33 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings that over 53 % of the patients were “normal presentation” patients concurs with previously published reports that a majority of elective referrals to paediatric orthopaedic specialists are for variants of normal development [ 33 ], and most are discharged after initial consultation [ 1 , 2 , 6 – 9 , 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…Several authors have cited a lack of confidence in musculoskeletal diagnostic skills amongst primary care physicians as a reason for the high rate of unnecessary referrals [ 21 – 28 ], and have called for improved musculoskeletal education as part of entry-level medical education. The American Academy of Paediatrics in 2002 published guidelines for primary care physicians on referral for specialist opinion [ 29 ], but subsequent studies found that this publication has had no effect on referral patterns [ 1 , 30 ]. It is within this context that new strategies are required to provide effective high-quality care for patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Poland's anomaly is the occurrence of unilateral absence or hypoplasia of the pectoralis major muscle with symbrachydactyly and does not have a genetic etiology. 4 Although symbrachydactyly predominantly involves the left hand, those cases occurring as a component of Poland's anomaly are primarily on the right side (61.1%). 4 Catena et al 4 demonstrated that 57.7% of patients with absent pectoralis major muscle had associated upper limb anomalies: 8% with hypoplastic hand and no functional or morphologic anomalies, 20.6% with symbrachydactyly and 5 functioning fingers with morphologic anomalies and limited motion, 14.9% with symbrachydactyly and some functioning fingers, and 4.6% with symbrachydactyly and absent or nonfunctioning fingers.…”
mentioning
confidence: 99%
“…PS patients present with pectoralis muscle agenesis/hypoplasia, more frequently on the right side. PS can be associated with a variable degree of ipsilateral thoracic and/or upper limb anomalies [1, 2]. Incidence of PS has been reported between 1/20,000 and 1/30,000 births with a higher prevalence in males [3, 4].…”
Section: Introductionmentioning
confidence: 99%